Democracy in Latin America : Between Hope and Despair - Walker, Ignacio (Book collections on Project MUSE., 2013)
This book explores both the possibilities and difficulties of establishing a stable democracy in Latin America. The author argues that, throughout the twentieth century, Latin American history has been marked by the search for responses or alternatives to the crisis of oligarchic rule and the struggle to replace the oligarchic order with a democratic one. After reviewing some of the principal theories of democracy based on an analysis of the interactions of political, economic, and social factors, the author maintains that it is primarily the actors, institutions, and public policies - not structural determinants - that create progress or regression in Latin American democracy. This book is organized by eight themes: independence and the establishment of democracy; the economic shift from exports to import substitution; democratic breakdowns, transitions, and consolidation; the double transition to democracy and trade liberalization in the 1980s and 1990s; institutions, democratic governability, and neopopulism; presidentialism and parliamentarism; the "new social question"; and the need for democracy of institutions. The author systematically addresses the abundant literature on democracy in Latin America, combining a scholarly perspective with real world experience that enhances the understanding of political and economic development in the region. -- Publisher's website.